Bimanual load carriage alters sway patterns and step width. (April 2020) - Baudendistel, Sidney T.; Grindstaff, Terry L.; Rosen, Adam B.; Yentes, Jennifer M.
Abstract: Many workplace falls occur during tasks involving carrying a load with both hands. Successful balance and gait during bimanual load carrying may be attributed to the adaptability of a system to navigate changing environments (e.g. construction site). This study investigates how bimanual load carrying affects adaptability of balance and gait, using 0%, 5%, and 10% of body mass in 14 young adults. Regularity of balance, and measures of range and center of pressure distance, and gait measures of stride length and step width were quantified using sample entropy. When carrying 5% load, anterior-posterior balance became less adaptable relative to 0%. As load increased from 0% to 5%–10%, step width narrowed and variability increased significantly, indicating possible increased fall risk while walking. Healthy, young adults may be at an increased risk of falls when carrying a load due to a loss in adaptability in a dynamic workplace environment. Highlights: Bimanual load carrying may increase fall risk while working in young adults. While standing, sway becomes less adaptable and more random. While walking, step width narrows and coincides with increased variability.